2020
DOI: 10.5937/arhfarm70-29277
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity of organic and inorganic nickel in pancreatic cell cultures: Comparison to cadmium

Abstract: Nickel compounds are Group 1 carcinogens and possibly cancer-causing in the pancreas. We examined the toxicity of nickel in both 2-D and 3-D pancreatic cell cultures, to determine the LD50 for organic and inorganic nickel in normal and cancerous cells. Assays with cadmium chloride were performed to be a comparison to potential nickel-induced toxicity. Cells were exposed to twelve concentrations of NiCl2 or Ni-(Ac)2 for 48h (2-D), or six concentrations for 48 hours (3-D). There was a significant (P=0.0016) diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 53 publications
1
5
0
Order By: Relevance
“…A growing body of evidence suggests that Ni and Ni-containing compounds are carcinogenic, a fact recognized by international organisations [ 13 ]. The toxicity and carcinogenicity of Ni is supported by our previous data [ 10 , 11 , 18 , 60 ], as well as other reports using different cell-line models representing different cancers [ 92 , 93 , 94 , 95 ]. The similarity between toxic mechanisms and our work in PDAC cell lines suggests that Ni may work through the Akt pathway, which is independent of FOXO1 activation [ 92 , 94 ].…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…A growing body of evidence suggests that Ni and Ni-containing compounds are carcinogenic, a fact recognized by international organisations [ 13 ]. The toxicity and carcinogenicity of Ni is supported by our previous data [ 10 , 11 , 18 , 60 ], as well as other reports using different cell-line models representing different cancers [ 92 , 93 , 94 , 95 ]. The similarity between toxic mechanisms and our work in PDAC cell lines suggests that Ni may work through the Akt pathway, which is independent of FOXO1 activation [ 92 , 94 ].…”
Section: Discussionsupporting
confidence: 86%
“…Considering the above results, elevated Ni levels in the body may cause a disturbance of Fe homeostasis, thereby increasing the concentration of this bio-element; this can be a starting point for a further cascade of events that leads to the development of pancreatic cancer. Another recent study suggested that the role of Ni should be further investigated by considering its possible epigenetic effects [ 18 ]. The study implied that Ni could be involved in the malignant transformation of pancreatic cell cultures, but also highlighted the importance of toxicants affecting the cells at the same time as Ni, as the endpoint seemed to depend on the presence of other toxicants, as well as Ni concentration.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some of these risks include chronic pancreatitis development, diabetes mellitus, and some infectious diseases [19]. Additionally, environmental exposures can induce PDAC development through various mechanisms, such as the inhalation of cigarette smoke, exposure to mutagenic nitrosamines or chlorinated hydrocarbon solvents, and exposure to toxic metals such as arsenic, nickel, and cadmium [20][21][22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%